Influence of Water Content on the Flow Consistency of Dredged Marine Soils - Mohammad Zawawi, Rosman; Siti Farhanah, SM Johan; Norsharina, Abdul Rahman; Chee Ming, Chan (EDP Sciences, 2016)
In present time, dredged marine soils (DMS) are generally considered as geo-waste in Malaysia. It is also known to contain high value of water and low shear strength. Lightly solidified soils such as soilcement slurry and flowable fill are known as controlled low strength materials (CLSM). On site, the CLSM was tested for its consistency by using an open-ended cylinder pipe. The vertical and lateral displacement from the test would determine the quality and workability of the CLSM. In this study, manufactured kaolin powder was mixed with different percentages of water. Cement was also added to compare the natural soil with solidified soil samples. There are two methods of flowability test used, namely the conventional lift method and innovative drop method. The lateral displacement or soil spread diameter values were recorded and averaged. Tests showed that the soil spread diameter corresponded almost linear with the increasing amount of water. The binder-added samples show no significant difference with non-binder sample. Also, the mixing water content and percentage of fines had influenced the soil spread diameter.